B32 Alterations in Mitochondrial Proteome of Brain and Skeletal Muscle in Two Transgenic HD Mouse Models do not Reflect Mitochondrial Respiratory Activity. (17th September 2014) - Barth, E; Fleischer, C; Lenk, T; Lehnert, S; Jahn, O; Otto, M; Calzia, E; Landwehrmeyer, GB; Lindenberg, KS
Abstract : Metabolic changes in HD pathogenesis and mitochondrial dysfunction are supposed to be closely linked. HD patients lose significantly body weight despite normal or even increased food intake and impairment of ATP synthesis occurs even in pre-motor manifest HD expansion mutation carriers. The molecular mechanisms linking mutant huntingtin to mitochondrial dysfunction are still not understood. In a previous study we have investigated the mitochondrial proteome of brain and skeletal muscle of the transgenic R6/2 mice and the HdhQ-Knock in mice using the 2D-DIGE (2-dimensional differential in-gel electrophoresis) approach. Differentially expressed mitochondrial proteins in R6/2 mouse brains and skeletal muscle belonged to the citric acid cycle, the amino acid degradation pathway, mitochondrial fusion and heat shock proteins. Surprisingly, the majority of these proteins were upregulated in the R6/2 mice. The mitochondrial proteome alterations in the knock-in mouse model HdhQ were similar, although the total number of differently expressed mitochondrial proteins was lower. The upregulation of mitochondrial proteins in the HD transgenic mice was confirmed for some selected proteins. In contrast, no significant changes in expression were found for these proteins in whole tissue lysate, although qPCR data showed a reduction of mtDNA copy number for brain and skeletal muscle of the transgenic mice. Using a high resolution respirometry approach the functional consequences of mitochondrial changes were further studied. Mitochondrial respiration under maximum stimulation of oxidative phosphorylation was unchanged in brain of HD mice, but was decreased in M. soleus. Our data suggest that an overall lower number of mitochondria is compensated by an upregulation of several metabolic pathways, reflecting at least in part compensatory changes. Interestingly, the activity of oxidative phosphorylation seems to be maintained in the brain, but not in skeletal muscle.